2004
DOI: 10.1111/j.1365-2133.2004.06142.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress is implicated in the pathogenesis of lichen sclerosus

Abstract: This is the first study to demonstrate oxidative damage to lipids, DNA and proteins in LS, revealing a novel pathophysiological mechanism which may contribute to sclerosis, autoimmunity and carcinogenesis. Therapeutic strategies using antioxidants might be a useful new approach in the treatment of LS and could also help to prevent secondary malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 31 publications
(59 reference statements)
1
80
0
4
Order By: Relevance
“…16 Another group of researchers compared vulval LS tissue from 16 patients with tissue from 16 vulval control samples and found a significant increase of lipid peroxidation products, particularly within epidermal basal cells, thus co-localizing with ECM-1. 17 The authors also demonstrated a significantly reduced expression of manganese superoxide dismutase, a mitochondrial enzyme that catalyses the reaction from superoxide anions to hydrogen peroxide. The enhanced oxidative stress caused by reduced enzyme expression could be a pathogenic factor in the autoimmune or neoplastic associations observed in some patients with LS.…”
Section: Other Suggested Factorsmentioning
confidence: 99%
“…16 Another group of researchers compared vulval LS tissue from 16 patients with tissue from 16 vulval control samples and found a significant increase of lipid peroxidation products, particularly within epidermal basal cells, thus co-localizing with ECM-1. 17 The authors also demonstrated a significantly reduced expression of manganese superoxide dismutase, a mitochondrial enzyme that catalyses the reaction from superoxide anions to hydrogen peroxide. The enhanced oxidative stress caused by reduced enzyme expression could be a pathogenic factor in the autoimmune or neoplastic associations observed in some patients with LS.…”
Section: Other Suggested Factorsmentioning
confidence: 99%
“…In LP, inflammatory cellular infiltrate, which mainly consists of CD4+ lymphocytes, is a well-known source of ROS (4). In high concentrations, ROS cause damage to endothelial cells and subsequently upregulate intercellular adhesion molecule 1 leading to the recruitment of T lymphocytes (5).…”
Section: Introductionmentioning
confidence: 99%
“…(Cancer Sci 2006; 97: 99 -105) E ight-hydroxy-2′-deoxyguanosine (8-OH-dG), also known as 7,8-dihydro-8-oxo-deoxyguanosine (8-oxo-dG), (1) has been proposed as a key biomarker of oxidative DNA damage relevant to carcinogenesis (1,2) and pathogenesis of autoimmune disorders. (3,4) This DNA damage is induced by the reactions of reactive oxygen species (ROS), such as hydrogen peroxide (H 2 O 2 ), superoxide anions ( ), singlet oxygen and hydroxyl radicals (·OH).Human skin is constantly exposed to environmental stresses, and is vulnerable to the effects of ROS generated by exposure to ultraviolet (UV) radiation.(5) Yamamoto et al (6) reported that the formation of 8-OH-dG in DNA might be one of the mechanisms of daylight-induced mutagenesis. In fact, irradiation with a fluorescent sun lamp or with UVB does induce 8-OH-dG in the epidermis of hairless mice.…”
mentioning
confidence: 99%
“…(Cancer Sci 2006; 97: 99 -105) E ight-hydroxy-2′-deoxyguanosine (8-OH-dG), also known as 7,8-dihydro-8-oxo-deoxyguanosine (8-oxo-dG), (1) has been proposed as a key biomarker of oxidative DNA damage relevant to carcinogenesis (1,2) and pathogenesis of autoimmune disorders. (3,4) This DNA damage is induced by the reactions of reactive oxygen species (ROS), such as hydrogen peroxide (H 2 O 2 ), superoxide anions ( ), singlet oxygen and hydroxyl radicals (·OH).…”
mentioning
confidence: 99%
See 1 more Smart Citation